A Foresight Study on Automated Storage and Retrieval System in Warehouse Automation in Johor - Tam, Sau En; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2025)
With the rapid development of science and technology, many industries have begun to use automation technology and adopt intelligence to improve operational efficiency and reduce workplace accidents. Warehouse management systems have entered a new era, where automated storage and retrieval systems (ASRS) play a crucial role in warehouse automation. This advanced system utilizes the latest automation technologies to transform traditional warehouse management, enabling intelligent processing and efficient operations. As enterprises demand more intelligent warehouse solutions, ASRS is becoming increasingly important. However, there is limited research on ASRS implementation in Johor. This study aims to determine the trends, challenges, and key driving factors of ASRS in warehouse automation in Johor, Malaysia. It explores the future landscape of ASRS adoption by engaging key stakeholders in the Johor warehouse industry. Both quantitative and qualitative research methods were used, with data collection through surveys and analysis using the Statistical Package for the Social Sciences (SPSS). The STEEPV framework was applied to identify the significant drivers influencing ASRS development. The findings provide insights into the critical factors shaping ASRS adoption in Johor, highlighting opportunities and challenges for businesses. This study contributes to understanding how ASRS can enhance warehouse automation and offers recommendations for future improvements.